Factors Influencing The Choice Of Ophthalmology As A Career Amongst Students Of Dow University Of Health Sciences, Karachi - Hamidullah Ariff; Khowaja Faiz-ur-Rab; Shehlaa Dareshani; Tarique Saleem; Masood Hussain Rao (Journal of Bahria University Medical and Dental College)
Objective: To determine the factors influencing the choice of Ophthalmology as a career amongst Dow University of Health Sciences, Karachi. Study design and Setting: A descriptive cross sectional study was conducted on fourth and final year students of Dow Medical College, DUHS, Karachi through non-probability consecutive sampling technique. Methodology: Before conducting the study, permission from the Principal of Dow Medical College, Dow University of Health Sciences was taken. Overall 244 students were selected willing to participate in the study after having their written consent. A structured questionnaire with minor modification and after pretest was provided to them. All the information was filled by the student on their own reliability. The collected data was analyzed through SPSS version 21.0. The quantitative data was assessed through mean and standard deviation whereas frequencies and percentages were developed for qualitative data. Chi square test was applied to determine any significant correlation between different variables. Result: According to analysis of the data, 77% female and 23% male medical students of fourth and final year participated in the study. Overall 8.65% students were given their first choice of Ophthalmology which is at 4th rank in all specialties after internal medicine, cardiology and paediatrics. The major factors which influence them to select Ophthalmology as their first choice were high income, less working hours and experience of medical and surgical field. The major factors, which restrict them not to choose Ophthalmology as a career, wereless opportunity of residency, long duration of residency and less opportunity at private sector. Conclusion: Ophthalmology is at 4th rank in the choice of participated medical students. The factors attracted them to choose it were high income, less working hours and no night shift. However less opportunity of residency and less working opportunity at private sector restricted them not to choose the ophthalmology as their career.